Improved retinal and visual function following panmacular subthreshold diode micropulse laser for retinitis pigmentosa - Luttrull, Jeffrey K. (Eye (Lond), 2018)
OBJECTIVES: To examine the effect of subthreshold diode micropulse laser (SDM) on pattern electroretinography (PERG) and visual function in retinitis pigmentosa (RP). METHODS: The records of all patients (pts) undergoing SDM in a vitreoretinal subspecialty practice were reviewed. Inclusion criteria included the presence of RP evaluated before and after SDM by PERG. As a secondary outcome measure, the results of automated omnifield resolution perimetry (ORP) were also reviewed. RESULTS: All eyes undergoing SDM for RP were eligible study, including 26 eyes of 15 pts; seven male and eight female, aged 16–69 (avg. 47) years. Retinal function by PERG improved by all indices, with significant improvements in the 24° field signal latency measures; the MagD(µV)/ Mag(µV) ratio (P < 0.0001) and the MagD(µV) amplitude (P = 0.0003). ORP significantly improved by all indices (p = 0.02–0.002). Average best-corrected chart visual acuities improved from 0.6 to 0.4 logMAR units (p = 0.02). There were no adverse treatment effects. CONCLUSIONS: SDM significantly improved chart visual acuity, mesopic logMAR visual acuity perimetry, and retinal function by PERG in RP without adverse treatment effects. Treatment responses indicate a significant capacity for rescue of dysfunctional retina. These results suggest that early and periodic treatment with SDM might slow disease progression and reduce long-term vision loss.